A Simple and Improved HPLC-PDA Method for Simultaneous Estimation of Fexofenadine and Pseudoephedrine in Extended Release Tablets by Response Surface Methodology - Ruhul Kayesh; A. S. M. Moniruzzaman Sarker; Md. Zakir Sultan; Md. Sarowar Jahan (Journal of Chemistry)
A simple RP-HPLC method has been developed for simultaneous estimation of fexofenadine and pseudoephedrine in their extended release tablet. The method was developed based on statistical design of experiments (DoE) and Response Surface Methodology. Separation was achieved on double end-capped C18 column (250 mm × 4 mm, 5 μm). In this experiment, two components of mobile phase, namely, acetonitrile (% v/v) and methanol (% v/v), were the factors whereas retention and resolution of the chromatographic peaks were the responses. The effects of different composition of factors on the corresponding responses were investigated. The optimum chromatographic condition for the current case was found as an isocratic mobile phase consisting of 20 mM phosphate buffer (pH 6.8) and acetonitrile and methanol in a ratio of 50 : 36 : 14 (% v/v) at a flow rate of 1 mL/min for 7 minutes. The retention of pseudoephedrine and fexofenadine was found to be 2.6 min and 4.7 min, respectively. The method was validated according to the ICH and FDA guidelines and various validation parameters were determined. Also, forced degradation studies in acid, base, oxidation, and reduction media and in thermal condition were performed to establish specificity and stability-indicating property of this method. Practical applicability of this method was checked in extended release tablets available in Bangladeshi market.